An ecocritical reading of Margaret Atwood's The Handmaid’s Tale and Amitav Ghosh's The Hungry Tide - Nawar, Ariana (BRAC University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.